SUBHAT INCOME OF SHARIA FINANCIAL INSTITUTIONS ACCORDING TO DUAL LAW (Formal and Sharia Law) - Nurhadi Nurhadi (Universitas Islam Negeri Jakarta, 2019)
The research aims to determine the purpose of non-halal funds in the business of Islamic finance, as well as a review of the philosophy of Islamic law. The research method uses descriptive qualitative concepts, types of Risert library research, data collection using primary and secondary, and technical data analysis using the analysis contents method, with a measure of benefit (philosophy of Islamic law). The result is that non-halal funds are any income originating from non-halal businesses (al-Kasbu al-Ghairi al-Masyru'). Use for the benefit of the ummah or the social interests of the community. While the review of Islamic law philosophy of non-halal funds is if the halal funds are more dominant, then all of these funds become halal, if the halal funds are the same or less, then the percentage of illicit funds must be issued. While the remaining funds are lawful, this is because of General al-Balwa, Raf'ul Haraj Wal Hajah al-Ammah, Muro'at Qowa'id al-Katsrah Wa al-Ghalabah and because of the rules about tafriq shafqah (separating halal transactions from those haram). Subhat income according to dual law, halal according to formal and sub-law according to sharia law.